Modern Sensing Technologies - Mukhopadhyay, Subhas Chandra; Jayasundera, Krishanthi P.; Postolache, Octavian Adrian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an overview of modern sensing technologies and reflects the remarkable advances that have been made in the field of intelligent and smart sensors, environmental monitoring, health monitoring, and many other sensing and monitoring contexts in today's world. It addresses a broad range of aspects, from human health monitoring to the monitoring of environmental conditions, from wireless sensor networks and the Internet of Things to structural health monitoring. Given its breadth of scope, the book will benefit researchers, practitioners, technologists and graduate students involved in the monitoring of systems within the human body, functions and activities, healthcare technologies and services, the environment, etc. .
Non-Invasive Monitoring of Glycogen in Real-Time Using an Electromagnetic Sensor -- Sensors for Implants: Real-Time Failure Detection on the Arabin Pessary -- Development and Application of an Orthodontic Photometer and Thermometer to Monitor the Effect of Near Infrared Light on Root Resorption and Orthodontic Tooth Movement -- Wide Band Antennae System For Remote Vital Signs Detecting Doppler Radar Sensor -- Smart Sensing and Biofeedback for Vertical Jump in Sports -- Spontaneous Facial Expression Analysis Using Optical Flow Technique -- Heart Sound: Detection and Analytical Approach Towards Diseases -- Serious Games Based on Kinect and Leap Motion Controller for Upper Limbs Physical Rehabilitation -- Microwaves and functional materials: a novel method to continuously detect metal ions in water -- Reusable Surface Acoustic Wave Immunosensor for Monitoring of Mite Allergens -- Performance Enhancement of Polypyrrole Based Nano-Biosensors by Different Enzyme Deposition Techniques -- PiezoresistivePressure Sensors for Applications in Harsh Environments -- Noncontact Temperature Sensing of Heated Cylindrical Rod by Laser-Ultrasonic Method -- Development of a PVDF multi-resonance vibration sensor with a wide range of frequency resolution -- Unique and Unclonable Capacitive Sensors for Nature-Inspired Secure Sensing -- Internet of Things Scalability: Communications and Data Management -- Internet of Things: Vision, Future Directions and Opportunities -- A Novel Unobtrusive Vibration Sensing System for Machine Inspection -- Compensation Techniques for Vibration Sensors with Application in Structural Health Monitoring.
Keywords: Telecommunication; Biomedical engineering; Environmental monitoring; Medical informatics; Biotechnology; Communications Engineering, Networks; Biomedical Engineering and Bioengineering; Environmental Monitoring; Health Informatics; Biotechnology